PENGARUH KEPEMIMPINAN SISWA TERHADAP PRESTASI BELAJAR SISWA DI SD NEGERI 1 TAIPABU - AMALUDDIN (Jurnal Pendidikan Sejarah, 2023)
The problem in this research is whether there is an influence of student leadership on student learning achievement at SD Negeri 1 Taipabu. The aim of this research is to determine the extent of the influence of student leadership on student learning achievement at SD Negeri 1 Taipabu. This research is a quantitative method, a type of correlational study. The population in this research is the entire number of students in grades IV and V at SD Negeri 1 Taipabu, which is 51 students. The sample for this research used a total sampling technique (total number) for class IV totaling 32 students, and class V totaling 19 students. The instruments and data collection techniques used in this research were observation and questionnaires The research results were analyzed quantitatively using the product moment formula. Based on the results obtained, the correlation coefficient (r) is 0.95, while the determination value (r2) is 90.25. Validity test of 0.371 can be concluded that there is student leadership towards student learning achievement at SD Negeri 1 Taipabu. The t-test is 1.419, so it can be concluded that there is an influence of student leadership on student learning achievement at SD Negeri 1 Taipabu. To test the reliability of the variable X instrument, the result was r = 5.4528. This is the average or mean, namely 68.35 and the r table, taking into account the magnitude of rxy = 0.95, which ranges from 0.800 – 1.000, means that there is a correlation between variables X and Y and that is a very high positive correlation.